The role of trust in leadership, knowledge sharing and quality of information systems on innovation and motivation of public library staff - Masarat Ayat; Maryam Soleimani; Mohammad Taghi Ghandehari (تحقیقات اطلاع‌رسانی و کتابخانه‌های عمومی, 2023)
Purpose: People who have a sense of trust in the leadership believe that they are treated fairly and with fairness and sincerity in the organization. These people are honest and transparent in their business communication, and their ability to listen to the opinions of others is more and better. Among the other factors that contribute to the increase of organizational quality and maturity, especially in organizations with information technology, is the quality of information systems and knowledge sharing. These three factors can be the basis for creation of creativity, motivation and promotion of knowledge in the organization. The purpose of this research is to investigate the effect of trust in leadership, knowledge sharing, and the quality of information systems on innovation and employee motivation in public libraries. Method: The current research is practical in terms of its purpose, and is quantitative-descriptive in terms of the type and method of collecting research data, and is based on the structural equation model (SEM) that was conducted using the survey method. The statistical population of the study included all the employees of the public libraries of Chaharmahal and Bakhtiari province in the year 1400 in the number of 148 people, which was sampled using a simple random sampling method and finally 113 complete questionnaires were analyzed. To collect data from the leadership trust questionnaire (Seo et al., 2016), information systems quality questionnaire (Delon and McLean, 2004), employee innovation questionnaire (Scott and Brath, 1994), employee motivation questionnaire (Bakhshi et al., 2004) and knowledge sharing questionnaire (Lee, 2001) was used. The content validity of the tool was verified by experts and its reliability was calculated using Cronbach’s alpha. Findings: In order to achieve the purpose of the research, eight sub-hypotheses were defined to fully evaluate and examine all aspects of the research. The findings showed that trust in leadership has a significant effect on employee innovation and motivation. In addition, the quality of information systems affects the innovation and motivation of employees. On the other hand, trust in leadership and the quality of information systems affect knowledge sharing, and knowledge sharing is also effective on employee innovation and motivation. Originality/value: The current research has investigated the effect of trust in leadership, knowledge sharing and the quality of information systems on innovation and motivation in all active public libraries in Chaharmahal and Bakhtiari province. This research is the the first study based on the combination of internal and external reference questionnaires that have dealt with the determining role of these factors in increasing the service quality of public libraries in Iran. In addition, the results of this research can help library managers to move the atmosphere of collaboration within the library towards more favorable conditions in the interaction between employees and provide more creativity and motivation for colleagues with appropriate policy making and planning. This policy itself can lead to a more appropriate response from library staff to clients.